Subsequent Treatment and Clinical Outcome Following Induction Therapy on a Phase II Study of Oral Azacitidine Plus CHOP for Peripheral T-Cell Lymphoma (PTCL) - Ruan, Jia; Orlando, Evelyn H.; Moskowitz, Alison; Chen, Zhengming; Mehta-Shah, Neha; Sokol, Lubomir; Horwitz, Steven; Rutherford, Sarah C.; Sahni, Tejasvi; Melnick, Ari M; Inghirami, Giorgio; Cerchietti, Leandro; et al. (Blood, 2024)
INTRODUCTION: We previously reported the efficacy including induction response rates (ORR 75% and CR 75%) and early survival outcome (2-yr OS 69% and 2-yr PFS 66%) of an exploratory phase II study of oral azacitidine (CC-486) plus CHOP as initial treatment for PTCL (ClinicalTrials.gov - NCT03542266; Blood 2023;141:2194-2205). Here, we report subsequent therapy following induction and long-term survival outcome at 5 years. METHODS: Study subjects received CHOP on day 1 of each cycle for 6 cycles. Oral azacitidine (aza) priming at 300 mg daily was administered for 7 days prior to C1 of CHOP, and for 14 days before CHOP C2-6. The primary endpoint was CR following 6 cycles of induction therapy per 2014 IWG criteria. Secondary endpoints included safety and survival. In this updated analysis, we reviewed long-term outcomes at 5 years post-treatment, including data on subsequent lines of treatment for patients who progressed after initial therapy. Survivals were estimated by Kaplan-Meier analysis, and log-rank tests were performed to correlate biomarkers to survival outcomes. Subsequent OS was measured from time of progression. RESULTS: A total of 21 subjects with previously untreated PTCL, including 17 with PTCL-TFH (81%), 3 with PTCL-NOS (14%), were enrolled and received treatment at 4 centers. Twenty subjects were evaluable for efficacy while 1 withdrew after 1 cycle. The median age was 66 years (range 22-77), 19 (90%) had stage III/IV disease, 10 (48%) had elevated LDH, 7 (35%) had bone marrow involvement, and 9 (43%) had IPI 3-5. As of July 2024 at a median follow-up of 54 months (range 41-65), 11 subjects progressed including 6 who underwent consolidative autologous stem cell transplant (autoSCT), 2 were lost to follow up without documented progression, and 8 deceased (including 3 from non-lymphomatous infectious complications). The median OS was 60 months (95% CI 15, NR), and median PFS was 40 months (95% CI 8, NR). The 5-year OS for the entire cohort of evaluable patients (n=20) was estimated at 61.1% (95% CI 37.8%, 84.3%), including 5-yr OS for PTCL-TFH (n=17) at 68% (95% CI 44.1%, 91.8%). The 5-yr PFS for the entire cohort was 26.3% (95% CI 2.2%, 50.5%), including 5-yr PFS for PTCL-TFH at 27.7% (95% CI 2.4%, 52.9%). For all patients, TET2 mutations were significantly associated with favorable PFS (p=0.004) and OS (p=0.002), while DNMT3A mutations and elevated LDH were associated with adverse PFS (p=0.016 and 0.012, respectively). Within PTCL-TFH, TET2 mutations were associated with favorable PFS (p=0.014) and OS (0.029), while elevated LDH was associated with adverse PFS (p=0.021). For the 11 evaluable patients who progressed, 10 relapsed with the same PTCL histology, while one patient who had PTCL-TFH relapsed with DLBCL. Subsequent salvage regimens for the 10 relapsed PTCL patients included: duvelisib single agent (n=1), duvelisib + romidepsin (n=2, one moved on to alloSCT), duvelisib plus ruxolitinib (n=1), romidepsin + BV followed by alloSCT (n=1), single agent sequences of romidepsin, bendamustine, duvelisib, followed by BV-DICE (n=1), romidepsin plus azacitidine sequenced with single agent bendamustine, followed by BV-DICE (n=1), high dose methotrexate-based regimen with modified MATRIX without rituximab for CNS relapse (n=1), phase 1 clinical trial (n=1), and palliation (n=1). The one patient with relapsed DLBCL was treated with R-DHAX 2 cycles, polatuzumab vedotin/bendamustine/rituximab 2 cycles, followed by CAR-T (Yescarta). Subsequent OS ranged from 7 to 56 months, with median estimated at 50 months (95% CI 7, NR). CONCLUSIONS: Data from the 5-year follow-up of the phase 2 oral azacitidine plus CHOP exploratory study suggests that lymphoma relapses occurred without a plateau for most PTCL-TFH patients who achieved remission during induction. Subsequent treatments following relapses were notable for salvage sequences incorporating novel agents as well as allogeneic stem cell transplant, which may benefit to extend survival in this cohort. These preliminary response and survival outcome data is being evaluated in a larger and randomized trial, the ALLIANCE/ US Intergroup randomized study A051902, comparing oral azacitidine-CHO(E)P vs duvelisib-CHO(E)P against CHO(E)P in PTCL patients expressing CD30<10%. Ruan:AstraZeneca: Honoraria, Research Funding; Janssen: Honoraria; Genentech: Research Funding; BMS: Honoraria, Research Funding. Moskowitz:Takeda Therapeutics: Honoraria; Tessa Therapeutics: Honoraria; Secura Bio: Research Funding; ADC therapeutics: Research Funding; Miragen Therapeutics: Honoraria; Seattle Genetics: Honoraria, Research Funding; Beigene: Research Funding; Merck: Research Funding; Incyte: Research Funding; Brystal-Meyers Squibb: Research Funding. Mehta-Shah:Daiichi Sankyo: Consultancy, Research Funding; Dizal Pharmaceuticals: Research Funding; Genetech/Roche: Consultancy, Research Funding; Morphosys: Research Funding; Innate Pharmaceuticals: Research Funding; Johnson & Johnson/Janssen: Consultancy; Pfizer: Consultancy; Secura Bio: Consultancy, Research Funding; Yingli Pharmaceuticals: Research Funding; Celgene: Research Funding; C4 Therapeutics: Consultancy, Research Funding; Astra Zeneca: Consultancy, Research Funding; Bristol Myers-Squibb: Research Funding; Verastem Oncology: Research Funding; Corvus Pharmaceuticals: Research Funding; Kyowa Hakko Kirin, Karyopharm Therapeutics: Consultancy. Sokol:CRISPR Therapeutics: Consultancy; Kyowa Kirin, Inc: Consultancy, Research Funding; EUSA: Research Funding. Horwitz:Auxilius Pharma, Abcuro Inc., Corvus, CTI BioPharma Corp, Daiichi Sankyo, DrenBio, Kyowa Hakko Kirin, March Bio, ONO Pharmaceuticals, Pfizer, SecuraBio, SymBio and Takeda Pharmaceuticals.: Honoraria; Auxilius Pharma, Abcuro Inc., Corvus, Daiichi Sankyo, DrenBio, Farallon Capital Management, L.L.C., Kyowa Hakko Kirin, March Bio, Neovii Pharmaceuticals AG, ONO Pharmaceuticals, Pfizer, SecuraBio, SymBio, Treeline Bio and Takeda Pharmaceuticals.: Consultancy; ADC Therapeutics, Affimed, Celgene, Crispr Therapeutics, Daiichi Sankyo, Kyowa Hakko Kirin, Takeda, Seattle Genetics, Trillium Therapeutics, and SecuraBio.: Research Funding. Rutherford:Constellation: Research Funding; ADC Therapeutics: Consultancy; Genentech: Research Funding; Karyopharm: Consultancy, Other: DSMB, Research Funding; BMS: Consultancy; Genmab: Consultancy; Kite: Consultancy; Seagen: Consultancy; Pfizer: Consultancy. Melnick:Daiichi Sankyo: Consultancy; Ipsen (formerly Epizyme): Consultancy, Research Funding; Exsciencia AI Ltd.: Consultancy; Astra Zeneca: Research Funding; Janssen Global Advisory: Membership on an entity's Board of Directors or advisory committees; Treeline Biosciences: Consultancy. Inghirami:Daiichi Sankyo: Consultancy. Leonard:AbbVie, AstraZeneca, Astellas, Bayer, BeiGene,BMS, Calithera, Constellation, Eisai, Epizyme,GenMab, Grail, Incyte, Janssen, Karyopharm, Lilly,Merck, Mustang Bio, Pfi zer, Roche/Genentech,Seagen, Second Genome, Sutro: Consultancy. Martin:AbbVie, AstraZeneca, Beigene, Daiichi Sankyo, Genentech, Janssen, Merck, Pepromene: Consultancy. CC486, oral azacitidine, as frontline treatment for peripheral T-cell lymphoma.